THE EFFECTIVENESS OF USING WORD MAPPING STRATEGY IN INCREASING STUDENTS’ VOCABULARY MASTERY AT SMP NEGERI 3 KAPONTORI - Muhammad Zakaria Edy; Esa Penilta Amiruddin (English Education Journal, 2019)
Lack of vacabularies effects the learners in understanding English. The aim of this study was to find out the effectiveness of using word mapping strategy in increasing students’ vocabulary mastery at SMP Negeri 3 Kapontori. This study used Pre-Experimental design. The population was students of class VIII SMP Negeri 3 Kapontori academic year 2019/2020. T-test was used for analyzing the data. Research findings showed ttest was lower than ttable (-13.248 < 2.079). In conclusion, word mapping strategy effect positively on students’vocabulary mastery at SMP Negeri 3 Kapontori.